Dampak Perkembangan Demokrasi Indonesia Terhadap Sila Persatuan Indonesia - Ivana Theo Philia; Yakobus Ndona (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to see the impact of the development of Indonesian democracy on the Principles of Indonesian Unity. As the world's largest democracy with a large population and cultural, religious and ethnic diversity, Indonesia has experienced significant political change since the 1998 reforms. As part of this transition, Indonesia adopted Pancasila as the basis of the state. Pancasila contains five commandments, one of which is the principle of Indonesian Unity. The development of democracy in Indonesia has had a significant impact on the implementation of the values ​​of the Principles of Unity. Through a democratic process that continues to develop, various elements of society have the opportunity to participate in nation building and express their opinions and desires in political decision making. The method for writing this research uses library research, namely a method of collecting data by understanding and studying theories from various literature related to research. The results of this research are that the development of Indonesian democracy has had a significant positive impact on the Principles of Indonesian Unity. The Principles of Indonesian Unity have become more effective in building unity and oneness amidst existing diversity, as well as increasing the protection of human rights and awareness of equality between citizens.